Economical and environmentally-friendly approaches for usage of onion (Allium cepa L.) waste. Issue 8 (26th July 2016) - Sharma, Kavita; Mahato, Neelima; Nile, Shivraj Hariram; Lee, Eul Tal; Lee, Yong Rok
Abstract : General anatomy and different layers in onion. Abstract : Onion ( Allium cepa L.) is one of the most commonly cultivated crops across the globe, and its production is increasing every year due to increasing consumer demand. Simultaneously, huge amounts of waste are produced from different parts of the onion, which ultimately affect the environment in various ways. Hence, proper usage as well as disposal of this waste is important from the environmental aspect. This review summarizes various usage methods of onion waste material, and processes involved to achieve maximum benefits. Processing industries produce the largest amount of onion waste. Other sources are storage systems, domestic usage and cultivation fields. Particular emphasis has been given to the methods used for better extraction and usage of onion waste under specific topics: viz . organic synthesis, production of biogas, absorbent for pollutants and value added products.